A more rational selection of the behaviour factor for seismic design according to Eurocode 8. (1st June 2019) - Macedo, L.; Silva, A.; Castro, J.M.
Highlights: A rational selection of the q-factor for the design of steel MRFs is evaluated. Selection method considers the seismic demand and building characteristics. EC8-prescribed q-factors may lead to significant overstrength levels. Improved q-selection methodology may result in relevant material savings. The methodology leads to acceptable levels of building collapse performance. Abstract: The main objective of the research presented in this paper is to assess the influence of a more rational selection of the behaviour factor ( q ) for the seismic design of steel moment-resisting frames (MRFs) according to Eurocode 8 (EC8). To this end, a large set of steel MRFs were designed using for code-prescribed behaviour factors as well as using the Improved Force-Based Design (IFBD) methodology for a more consistent selection of q . The seismic performance of the archetypes was assessed through nonlinear static and response-history analysis. The results point to the discrepancy between the design assumptions and the real response of the structures, as significant differences between the design base shear and the lateral strength of the frames were observed for frames designed with code-prescribed behaviour factors. Moreover, it is shown that IFBD-designed steel frames exhibit more uniform inelastic demands over the building height, as well as ductility demands more compatible with the design assumptions. Finally, the fragility and seismic risk assessment conducted shows that all building archetypes, regardless of the q -scenario considered, exhibit values of mean annual frequency of collapse that comply with limits available in the literature.